Organizational trust as a determinant of the relationship between organizational justice and behaviorally organizational citizenship - Lecturer. Dr. Jasim Saad Jasim (Global Scientific Publishing, 2024)
The main research problem is the importance of studying the reality of organizational justice and organizational trust for the Directorate of youth and sports in Dhi Qar governorate and its impact on the behaviors of organizational citizenship in order to improve its position in society, raise its competitiveness, make its outputs distinguished by quality, increase the degrees of loyalty and affiliation among its employees in order to raise their performance level, and the aim of this research is to find out the size of the interactive impact of organizational trust as an intermediate variable on the relationship between organizational justice and organizational citizenship among employees of the Directorate of youth and sports in Dhi Qar governorate and measure the levels of the variables studied, and research on an intentional sample composed of employees in The Directorate of youth and sports in Dhi Qar governorate distributed (133) questionnaires designed by the researcher and after analyzing the results, it turned out that the results of the respondents were average in terms of organizational justice, as the employees of the Directorate of youth and sports have a good level of perception of the extent to which the Directorate's administration applies it, not to mention the regulatory
Keywords: Organizational trust; Organizational justice; behaviorally organizational citizenship lecturer